Cost-effectiveness of lipid-lowering therapies for cardiovascular prevention in Germany - Michaeli, Daniel; Michaeli, Julia; Boch, Tobias; Michaeli, Christoph T. (Cardiovascular drugs and therapy, 2023)
Novel pharmaceutical treatments reducing cardiovascular events in dyslipidaemia patients must demonstrate clinical efficacy and cost-effectiveness to promote long-term adoption by patients, physicians, and insurers.
Online veröffentlicht: 11. Januar 2022
Gesehen am 09.07.2024